Searching for genetic association using (haplotype) tagging SNPs - Clayton, David (Henry Stewart Talks, 2004)
The htSNP approach, R-square criterion for assessment, Power, Complexity vs. accuracy, Case studies: 4 gene regions, From htSNPs to causal variants, Quantitative traits, 1 df for dominance
Archived at 2021/02/25